PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP LOYALITAS MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Achmad Fauzan Wahyudianto; Ngatno Ngatno (Universitas Diponegoro, 2019)
Honda as one of the top car producer in the country needs to maintain customer loyalty to continue to survive in the midst of intense competition. Brand image has meaning to a consumer's mind images of a product. Everyone will have thir own standar of Product Quality that determines its value in the eyes of the community about the product. Customer loyalty is a form of customer loyalty to continue using products derived from the same company. Honda as one of the featured cars in the country needs to maintain customer loyalty to continue to survive in the midst of intense competition. This study aimed to determine the effect of brand image (X1) and Product Quality (X2) to Loyalty (Y) through the Customer Satisfaction (Z) user Honda Brio in the city of Semarang. This type of research uses explanatory research with data collection through interviews and data collection tools using a questionnaire. Sources of data in this study are primary data and secondary data. The sampling technique in this study using purposive sampling and non-probability sampling. The sample in this study amounted to 100 respondents in Semarang. Technical analysis using simple linear regression, multiple linear regression, t test and F test with SPSS. From the results of the study indicate that Brand Image (X1) has a significant effect on loyalty (Y), and Product Quality (X2) have a significant effect on loyalty (Y), The results also show that there is significant influence between brand image and product quality together to Loyalty (Y). Customer Satisfaction (Z) also have a significant effect on loyalty (Y). Based on the results of the study, the researchers suggested that the Honda is listening to the voice of the resilience of its product users in this study where the users often complain about dynamo radiator fan is often problematic. It is also expected Honda Being able to change some of the components that looks cheap to be an advantage over its competitors.